EVALUASI PENERAPAN E-COMMERCE PADA PERUSAHAAN DISTRIBUTOR PT PANAHMAS DWITAMA DISTRINDO JEMBER - Yeha Reine Nabilah Adiratna; Sukaris Sukaris (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The digital era has caused people's shopping patterns to change from offline to online. Many companies are competing to establish e-commerce to meet the ever-increasing online market. PT. Panahmas Dwitama Distrindo Jember is a manufacturing product distribution company PT Unilever Indonesia which dominates the market in Jember and its surroundings, and has also implemented an e-commerce called Panahmas Warung since 2020. This descriptive qualitative research method aims to evaluate how the application of e-commerce supports the success of Panahmas marketing in developing the market. As a result, Panahmas Warung was not managed seriously, so it ran static, and the application was discontinued in 2022. The reason for stopping the Panahmas Warung application was allegedly due to its inability to develop the company's market or business. There are many causes for Panahmas Warung's failure such as lack of human resources, lack of user interest, lack of promos, lack of collaboration and lack of social media utilization because the managing human resources are not adaptive to the latest technology. From the results of the research above, it can be concluded that as a consumer goods distributor company, PT Panahmas Dwitama Distrindo has quite a big opportunity in developing its business. This can be achieved if PT Panahmas Dwitama Distrindo utilizes online or e-commerce application channels in the form of a website or the company's official social media accounts which are managed professionally and consistently.